8(3a-52)-4(2a+3)=12

Simple and best practice solution for 8(3a-52)-4(2a+3)=12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8(3a-52)-4(2a+3)=12 equation:


Simplifying
8(3a + -52) + -4(2a + 3) = 12

Reorder the terms:
8(-52 + 3a) + -4(2a + 3) = 12
(-52 * 8 + 3a * 8) + -4(2a + 3) = 12
(-416 + 24a) + -4(2a + 3) = 12

Reorder the terms:
-416 + 24a + -4(3 + 2a) = 12
-416 + 24a + (3 * -4 + 2a * -4) = 12
-416 + 24a + (-12 + -8a) = 12

Reorder the terms:
-416 + -12 + 24a + -8a = 12

Combine like terms: -416 + -12 = -428
-428 + 24a + -8a = 12

Combine like terms: 24a + -8a = 16a
-428 + 16a = 12

Solving
-428 + 16a = 12

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '428' to each side of the equation.
-428 + 428 + 16a = 12 + 428

Combine like terms: -428 + 428 = 0
0 + 16a = 12 + 428
16a = 12 + 428

Combine like terms: 12 + 428 = 440
16a = 440

Divide each side by '16'.
a = 27.5

Simplifying
a = 27.5

See similar equations:

| -9n-10=-100 | | 12x+11=14x+1 | | 17t+15=11t+51 | | 6y-15=-5y+18 | | (4n-1)(2n+4)= | | 4y+4=3y-6 | | 8x+3=13+3x | | (5a^2x+3ax^2-5x)+(2a^2x-5ax^2+7x)= | | 12x-10=62 | | -5(X+3)2(x-1)=-14 | | 8(2)+5= | | -9w-19=4w-6 | | -9-(4)(2)(x)=3249 | | 8x^2-21x+10=0 | | 8x^2-1x-9=0 | | 10w+16=10w+16 | | 3.2q-4.1-4.6q=-2.4q-3.2 | | 1+p+5+p=-2 | | 6r(2r-1)= | | 5x+24=12x+60 | | 6m+10=25-m | | 5x+11=12x+60 | | (5x^2-x-7)+(2x^2+3x+4)= | | 20e+50f=8(40) | | 22x-26x=10-14 | | -10-8x=-110+6 | | 3x-5y-4y+9x+2= | | 2xa-11=-5 | | 5x=48+2x | | (5x+3o)+9o= | | -3(4)+-2=x | | -(x-1)-4(x-3)=58 |

Equations solver categories